THE ITALIAN RENAISSENCE OF THE NUCLEAR OPTION — HOPE OR DESPAIR - Milocco, Alberto; Trkov, Andrej (Journal of Energy Technology, 2024)
On 15 February 2010, the Italian government enacted a legislative decree on the site evaluation, commissioning and operation of nuclear facilities. The decree, de jure and de facto, opened the road for the construction of new nuclear power plants, which had been abandoned from the time of the Chernobyl accident. This decision is relevant considering the present social movements in northern Africa and the nuclear accidents at Fukushima. An entirely new nuclear program started, but its continuation is currently hampered by the outcome of a popular referendum, which took place on 12 and 13 June 2011 and addressed the specific issues of the legislative decree of 15 February 2010. The Italian involvement in the context of nuclear energy is still alive in the area of nuclear research, decommissioning and the management of nuclear projects abroad.